The border dispute between Senegal and Mauritania between 1989 – 1991 - bouchelaghem, fouad; saadouni, bachir (The Algerian Historical Journal, 2026)
The follower of African events understands the multiplicity of conflicts in the continent, as well as the different nature of these conflicts and their causes, which leads to the different means of settlement.On the one hand,and its sensitivity, on the other hand,despite the occurrence of many tensions and disputs historically between Mauritania and Senegal, which were visible on the horizon since 1985 and the outbreak of the crisis in 1989 as a result of the excesses of Senegalse farmers and Mauritanin herders, the successive governments in both countries,it worked to reduce the chances of conflict or conflict erupting.and to prevent the situation from deteriorating by setting these disputes quickly